2008
DOI: 10.1111/j.1469-7580.2008.00991.x
|View full text |Cite
|
Sign up to set email alerts
|

A three‐dimensional microcomputed tomographic study of site‐specific variation in trabecular microarchitecture in the human second metacarpal

Abstract: Variation in trabecular microarchitecture is widely accepted as being regulated by both functional (mechanical loading) and genetic parameters, although the relative influence of each is unclear. Studies reporting intersite differences in trabecular morphology (volume, number and structure) reveal a complex interaction at the gene-environment interface. We report inter-and intra-site variation in trabecular anatomy using a novel model of contralateral (left vs right) and ipsilateral (head vs base) comparisons … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 36 publications
(45 reference statements)
1
15
0
Order By: Relevance
“…This variability is likely to have influenced the results of the current study. Future investigations of this type may consider assessing more constrained joints in the skeleton (Carlson et al, 2008a;Lazenby et al, 2008;Griffin et al, 2010;. The hind limb dominance of most anthropoids undoubtedly influences the distribution of cortical bone robusticity and trabecular bone architectural properties.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This variability is likely to have influenced the results of the current study. Future investigations of this type may consider assessing more constrained joints in the skeleton (Carlson et al, 2008a;Lazenby et al, 2008;Griffin et al, 2010;. The hind limb dominance of most anthropoids undoubtedly influences the distribution of cortical bone robusticity and trabecular bone architectural properties.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of both sub-articular trabeculae and diaphyseal cortical bone is a relatively new approach (see Carlson and Judex, 2007;Carlson et al, 2008a;Lazenby et al, 2008) that allows for direct comparisons of morphological variation in two types of osseous tissue, within the same skeletal element. The integrated consideration of diaphyseal and trabecular bone properties is a perspective that attempts to move away from the reductionism that often occurs with trabecular bone analyses in the comparative literature.…”
Section: Focus Of This Studymentioning
confidence: 99%
“…Trabecular connectivity and structure are calculated in a similar way and are highly correlated (Lazenby et al. 2008a), thus it is not unexpected that they are equally affected by changes to the VOI.…”
Section: Discussionmentioning
confidence: 99%
“…2007; Scherf & Hublin, 2007; Scherf, 2008; Scherf et al. 2009) and manipulative behaviors (Lazenby et al. 2008a,b), providing novel insight into the functional interpretation of both extant and fossil primate morphology (Ryan & Ketcham, 2002b; Scherf, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Our findings highlight that a level of activity or strength might be determined as a threshold to stimulate aptation to environment. Lazenby et al (2008a) suggest that volumetric variables such as BV/TV and Tb.N are sensitive to mechanical regulation and handedness. Further, they found that the influence of age is felt more on the left rather than the right metacarpal given the human propensity for right-handedness.…”
Section: Limitationsmentioning
confidence: 99%